The Effectiveness of the Implementation of the Program 3R (Reduce, Reuse, Recycle) In Waste Treatment In the District We the City of Palembang - Deby Chintia Hestiriniah; Trecy Austin (Brawijaya University, 2022)
The purpose of this study is to investigate and analyze the effectiveness of the Implementation of the Program 3R (reduce, reuse, recycle) in waste processing. This study was conducted in District We the City of Palembang. Research using this approach kualitatif with the level of explanation descriptive. As for the type of data used in this research included in this type of qualitative data. Data collection techniques used include in-depth interviews (indepth interview), observation and documentation. The data analysis technique used in this research is a descriptive technique which includes three stages of analysis, namely data reduction, data display and conclusion drawing/verification. From the research conducted, the processing of garbage through the program 3R proclaimed by the District We've been running effectively, it can be seen from the indicators of the effectiveness obtained by the researchers that the Level of Success of the Program, the Success Rate of the Target, the Level of satisfaction with the Program, the Level of Input and Output, and the Level of Achievement of the Objectives